Enhancing cowpea tolerance to elevated temperature: achievements, challenges and future directions - Mohammed, S.B.; Ongom, P.O.; Togola, A.; Boukar, O. (MDPI, 2024)
Despite its ability to thrive in high-temperature environments, cowpea productivity can be hampered by heat stress, particularly when night air temperatures exceed 17 °C. The crop’s germplasm pool potentially possesses significant genetic variability that can be harnessed to breed for heat-tolerant varieties. Progress in improving the crop for heat tolerance has been limited, especially under the hot, short-day environments typical of sub-Saharan Africa. Only a few heat-tolerant varieties have been released, partly due to the limited understanding of heat stress tolerance mechanisms and environmental interaction effects on genotypes, as well as imprecise phenotyping. This review contributes to the literature on cowpea heat stress by highlighting key achievements, challenges, and future directions in breeding heat-tolerant cowpea genotypes and by providing additional information from the recent literature. We opine that the genetic variability for heat tolerance-related traits in cowpea has not been sufficiently exploited in developing varieties adapted to the target production environments. Therefore, attention should be given to assessing the crop’s genetic repository by targeting adaptive, morphological, and physiological traits that enhance heat stress tolerance. We propose that breeding programs integrate phenotyping of whole-plant physiological traits and molecular breeding to identify breeder-friendly markers for routine selection. This should be followed by introgression of the heat-tolerant favourable alleles to adapted susceptible varieties using rapid and precise approaches that take advantage of modern genetic and genomic resources such as innovative genetic resources, genomic selection, speed breeding, and genome editing technologies. These tools hold great promise in fast-tracking the development of improved heat-tolerant varieties and incorporating the must-have traits preferred by cowpea farmers and consumers. In view of the likely increase in atmospheric temperature to be occasioned by climate change, there is an urgent need to develop heat-tolerant cowpea varieties to ensure the sustainability of current and future cropping and agri-food systems.